Induced sputum is a reproducible method to assess airway inflammation in asthma - Elena Bacci; Silvana Cianchetti; Stefano Carnevali; Maria Laura Bartoli; Federico L. Dente; Antonella Di Franco; Daniele Giannini; Barbara Vagaggini; Pier Luigi Paggiaro (Mediators of Inflammation)
To evaluate the reproducibility of induced sputum analysis, and to estimate the sample size required to obtained reliable results, sputum was induced by hypertonic saline inhalation in 29 asthmatic subjects on two different days. The whole sample method was used for analysis, and inflammatory cells were counted on cytospin slides. Reproducibility, expressed by intra-class correlation coefficients, was good for macrophages (+0.80), neutrophils (+0.85), and eosinophils (+0.87), but not for lymphocytes (+0.15). Detectable differences were 5.5% for macrophages, 0.6% for lymphocytes, 5.2% for neutrophils, and 3.0% for eosinophils. We conclude that analysis of induced sputum is a reproducible method to study airway inflammation in asthma. Sample sizes greater than ours give little improvement in the detectable difference of eosinophil percentages.